The hOGG1 Ser326Cys Gene Polymorphism and the Risk of Coronary Ectasia in the Chinese Population - Hsu, Po-Chao (Molecular Diversity Preservation International (MDPI), 2014)
Oxidative stress (OS) is related to vascular inflammation possibly, contributing to the development of coronary ectasia (CE). Base excision repair (BER) and nucleotide excision repair are the main DNA repair pathways that can help to remove 8-hydroxydeoxyguanine (8-OHdG), a marker of OS. Human 8-oxoguanine DNA glycosylase 1 (hOGG1) is a key enzyme of the BER pathway and catalyzes the removal of 8-OHdG. The aim of our study was to investigate the association between hOGG1 Ser326Cys gene polymorphism and CE in a Chinese population. Five-hundred forty-seven patients who underwent diagnostic coronary angiography in a tertiary medical center were recruited. The angiographic definition of CE is the diameter of the ectatic segment being more than 1.5 times larger compared with an adjacent healthy reference segment. The gene polymorphisms were analyzed by polymerase chain reaction. The urine 8OHdG concentration was measured using a commercial ELISA kit. The distribution of hOGG1 Ser326Cys genotypes was significantly different between CE and non-CE groups (p = 0.033). The odds ratio of CE development for the Ser to the Cys variant was 1.55 (95% confidence interval (CI), 1.04–2.31, p = 0.033). Both univariate and logistic regression analysis showed a significant association of hOGG1 Ser326Cys polymorphism in the dominant model with CE development (p = 0.009 and 0.011, respectively). Urine 8-OHdG levels were significantly higher in subjects carrying the hOGG1 Ser variant than in those with the Cys/Cys genotype (p < 0.03). In conclusion, our study suggests that the hOGG1 Ser326Cys gene variant might play a role in susceptibility to the development of CE.